2013
DOI: 10.1017/s0029665113003807
|View full text |Cite
|
Sign up to set email alerts
|

Healthy incentive scheme in the Irish full-day-care pre-school setting

Abstract: A pre-school offering a full-day-care service provides for children aged 0-5 years for more than 4 h/d. Researchers have called for studies that will provide an understanding of nutrition and physical activity practices in this setting. Obesity prevention in pre-schools, through the development of healthy associations with food and health-related practices, has been advocated. While guidelines for the promotion of best nutrition and health-related practice in the early years' setting exist in a number of juris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 93 publications
(127 reference statements)
0
6
0
1
Order By: Relevance
“…Nevertheless, improvements in food provision were achieved. The magnitudes of improvements in implementation of menus compliant with four of six individual food groups (fruit, meat and alternatives, dairy, discretionary) achieved by intervention services (21•5 % for fruit; 25•2 % for meat and alternatives; 22•5 % for dairy; 50•0 % for discretionary) were somewhat similar to yet slightly lower than those reported among trials using similar implementation strategies in childcare services to improve menus (40-68 %) (13,14,46,47) . The effect sizes were also similar to those reported in trials of implementation strategies in schools to improve the availability of healthy foods (25-42 %) (46,48) .…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Nevertheless, improvements in food provision were achieved. The magnitudes of improvements in implementation of menus compliant with four of six individual food groups (fruit, meat and alternatives, dairy, discretionary) achieved by intervention services (21•5 % for fruit; 25•2 % for meat and alternatives; 22•5 % for dairy; 50•0 % for discretionary) were somewhat similar to yet slightly lower than those reported among trials using similar implementation strategies in childcare services to improve menus (40-68 %) (13,14,46,47) . The effect sizes were also similar to those reported in trials of implementation strategies in schools to improve the availability of healthy foods (25-42 %) (46,48) .…”
Section: Discussionmentioning
confidence: 81%
“…Few trials, however, have been conducted to assess how to best support the implementation of nutrition guidelines in this setting. A recent Cochrane review (2017) found only two randomised trials of interventions targeting the implementation of dietary guidelines (13,14) . While both studies demonstrate that implementation strategies such as staff professional development and ongoing support may be effective at improving food provision, neither study measured the impact of improving food provision on child dietary intake.…”
mentioning
confidence: 99%
“…Differences between children’s dietary intake can be partially attributed to the childcare center the child is attending [ 16 ]. In view of the increasing use of childcare, various authors have called for increased attention for the influence of childcare practices on children’s dietary intake (e.g., [ 10 , 17 , 18 ]). An important social environmental influence on children’s dietary intake at childcare is staff behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The online supplementary material, Supplemental Table 5 shows the final CFAPQ. With regard to correlations between the CFAPQ and child-care staff's background characteristics, younger child-care staff scored higher on the activity-related scale Going outdoors (A-GO) than older staff (18)(19)(20)(21)(22)(23)(24)(25) n 116. Factors are labelled as follows: A-MOD, activity-related Modelling; A-PC, activity-related Psychological control; A-PST, activity-related Promote screen time; A-T/AS, activity-related Teaching/Autonomy support; A-GO, Activity-related Going outdoors.…”
Section: Associations Between the Cfapq And Background Characteristicsmentioning
confidence: 99%